Kita Adalah Saudara: Menyikapi Persoalan Kekerasan Agama Serta Pengaruhnya Terhadap Hubungan Antar Umat Beragama - Lumban Gaol, Rumondang (Sekolah Tinggi Diakones HKBP, 2024)
Indonesia has a plurality of tribes, races and religions. This certainly gives rise to many differences of opinion in the midst of today's plural society and in this case especially related to religion. Manipulation using religious identity is often used as a tool to legitimize violence, thus creating tension between religious communities. From year to year, acts of violation of religious freedom in Indonesia continue to increase. Therefore, in this context, a critical attitude is needed from the community to be able to read and understand the situation wisely, so as not to get caught up in a narrative that has the potential for violence and to open the paradigm of Indonesian society, especially Christians, on how to respond to the problem of religious violence that occurs in Indonesia. The purpose of this study is to build tolerance and love between religious communities. This research method uses a qualitative method.